Technology Culture and Digital Minimalism: An Analysis of Generation Z - Esra Şahin; Oya Morva (4. Boyut Medya ve Kültürel Çalışmalar Dergisi)
When defining culture as a particular way of life, the technology used has always directly impacted the way of life of the period to which it belongs. Technology has never been as integrated into culture as it is today. Digital technology, with its scope and pervasiveness, is an essential element in all practices in the daily life routine of an ordinary person. The way to exist in social life today depends on mastering the skills for using various digital technologies. The existence of such a social structure that demands and encourages the use of current technology at all levels creates a consciousness that suggests its use to be inevitable. On the other hand, the existence of alternative forms of use in the face of this encompassing nature of technology also needs to be mentioned. This study discusses the concept of digital minimalism, which is considered an alternative form of technology use, and addresses the questions of the reasons why individuals belonging to Generation Z in Türkiye turn to digital minimalism and how they use digital technology within this framework. In line with this, the study conducts in-depth interviews with 20 people (10 males, 10 females) who identify themselves as digital minimalists and analyzes the obtained data using the qualitative content analysis method. As a result, the research observes digital minimalism to have been evaluated and adopted as an alternative to the existing widespread use of technology and found it to include such practices as operating a self-control mechanism regarding the duration and intensity of technology usage, using purpose-oriented platforms, and developing different usage forms regarding the relevant technology or applications’ characteristics.